Characterizing changes in transcriptome and kinome responses in testicular cells during infection by Ebola virus - Andrew L. Webb; Brayden G. Schindell; Geoff Soule; Abu B. Siddik; Bernard Abrenica; Harram Memon; Ruey-Chyi Su; David Safronetz; Jason Kindrachuk (npj Viruses, 2024)
Abstract Ebola virus (EBOV) is able to persist and actively replicate in the reproductive tract of male disease survivors months or years after recovery from Ebola virus disease (EVD)1. Persistent EBOV infections are usually asymptomatic and can be transmitted sexually, but the host and viral factors that mediate these infections have not been characterized2,3. We investigated the interaction between host and viral factors during EBOV infection of the blood testis barrier (BTB), with a focus on Sertoli cells as a potential reservoir for viral persistence. We assessed viral replication kinetics and host responses of mouse testicular Leydig cells and Sertoli cells infected with EBOV Makona (i.e. infectious EBOV) and collected samples up to 28 days post-infection. Viral replication was apparent in both cell lines, but intracellular early viral loads were much higher in Leydig cells compared to Sertoli cells. We used RNAseq analysis to characterize transcriptomic responses of Leydig cells and Sertoli cells to EBOV infection over time. Further investigation of early interactions between host cells and EBOV was performed using virus-like particles (EBOV trVLP) and assays of phosphorylation-based cell signaling. Our findings indicate that virus-treated Sertoli cells responded more rapidly and robustly than Leydig cells, and with a particular emphasis on detection of, and response to, external stimuli. We discuss how the roles played by Sertoli cells in immune privilege and spermatogenesis may affect their initial and continued response to EBOV infection in a manner that could facilitate asymptomatic persistence.